Ecological Awareness of Nutmeg Tree (Myristica Fragrans Houtt) Through the Creation of Contemporary Batik Motifs - Cahyani, Isma Awal Fitroh; Rahmawati, Ria; Shiba, Asyfa Putri; Dayani, Elin Siska; Prasetya, Hanggar Budi (Dinamika Kerajinan dan Batik: Majalah Ilmiah, 2025)
The The diminishing presence of nutmeg tree nowadays has led to the neglect of the potential that they hold in the eyes of the community. Developing the visual potential of nutmeg fruits into work of art can serve as educational tool for conservation efforts. The creation of contemporary batik motif plays a role in preserving nutmeg tress, undertaken by batik craftsmen in the batik production homes of Sukabumi, West Java. This article will discuss the ecological awareness of nutmeg tree through the creation of contemporary batik motifs. A craftsman at the Lokatmala Batik production house takes the nutmeg tree as the inspiration for the distinctive Sukabumi batik motif called “Palawan”. The research aims to (1) Document and narrate the creative process of crafting the Palawan batik motif, (2) Illustrate and interpret the Palawan batik motif, and (3) Reveal the ecological awareness of nutmeg tree through the Palawan batik motif. The research findings explain that the creative process involves various stages, visualizing the batik motif using Sundanese aesthetic composition concepts, and indicating ecological awareness in the community including sensitivity, responsibility, and collaboration. These indicators emerge due to collaboration among various stakeholders advocating for nutmeg tree conservation. This research employs a qualitative case study method at the Lokatmala Batik house in Sukabumi, West Java. The observation process takes place in both the batik production house and the nutmeg plantation which is involving in-depth interviews and documentation searches related to nutmeg. To gather data on the ecological awareness of nutmeg tree, the researcher engages in participant observation, allowing direct observation of ecological awareness indicators within the community. The study reveals that creative ideas from artists can stem from issues or needs present in their environment, and by responding to these the resulting artwork carries deeper value, providing knowledge or narrative about the conservation of a local cultural object. Furthermore, collaboration and support from various parties contribute to the preservation of nutmeg tree, ensuring their recognition among the community and future generations. This extends beyond nutmeg plant species to encompass other local cultural elements.